2008
DOI: 10.1098/rstb.2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on litterfall, wood production and belowground carbon cycling in an Amazon forest: results of a throughfall reduction experiment

Abstract: The Amazon Basin experiences severe droughts that may become more common in the future. Little is known of the effects of such droughts on Amazon forest productivity and carbon allocation. We tested the prediction that severe drought decreases litterfall and wood production but potentially has multiple cancelling effects on belowground production within a 7-year partial throughfall exclusion experiment. We simulated an approximately 35-41% reduction in effective rainfall from 2000 through 2004 in a 1 ha plot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
316
2
20

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(366 citation statements)
references
References 40 publications
28
316
2
20
Order By: Relevance
“…Two recent manipulation experiments have attempted to address these questions by excluding a fraction of the incoming throughfall of precipitation to the soil in 1-ha rainforest plots in E. Amazonia (24)(25)(26). Both experiments shifted a rainfall regime typical of evergreen forest into one near to or within the savanna bioclimatic zone (Fig.…”
Section: Vegetation Response To a Drying Amazonmentioning
confidence: 99%
“…Two recent manipulation experiments have attempted to address these questions by excluding a fraction of the incoming throughfall of precipitation to the soil in 1-ha rainforest plots in E. Amazonia (24)(25)(26). Both experiments shifted a rainfall regime typical of evergreen forest into one near to or within the savanna bioclimatic zone (Fig.…”
Section: Vegetation Response To a Drying Amazonmentioning
confidence: 99%
“…Impacts of seasonal changes in precipitation have been reported in boreal forests (Gaul et al, 2008), arctic tundra (Schimel et al, 2004), tropical rainforests in the Amazon (Nepstad et al, 2002;Brando et al, 2006;Brando et al, 2008), oak savannas (Volder et al, 2010;Volder et al, 2013) and Mediterranean regions, such as Spain (Miranda et al, 2009b). Although grasslands, savannas and Mediterranean forests differ markedly in the timing of ambient precipitation and the length of the growing season, experiments suggest patterns can be found in responses to seasonal changes in precipitation, such as strong changes in water stress and productivity in warm or dry seasons and not in cool or wet seasons.…”
Section: Seasonal Changes In Precipitationmentioning
confidence: 99%
“…In fact, the ability of some areas of the Amazon rainforest to maintain high ET rates and, eventually, keep growing or begin leaf flushing (108) during the dry season does not guarantee that humid forest could be resilient to extreme and prolonged droughts. In situ observations of the impact of "natural" extreme droughts (109) and artificially induced droughts for several years (110)(111)(112) showed that forest responds with interruption of growth and mortality of some species during a prolonged drought period. The results of artificially induced and natural droughts have shown that the larger trees [diameter at breast height (dbh) > 30 cm], together with lianas, are the most vulnerable ones (112).…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%